Pembelajaran berbasis etnosains pada materi biologi untuk meningkatkan prestasi belajar siswa : kajian literatur - Alma Aliya Jacinda; Surtikanti, Hertien; Riandi (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Ethnoscience is not something new in the world of education, although it is rarely applied in learning. This article aims to describe the application of ethnoscience-based learning to biology material in improving student achievement. This article was written using the theoretical method of literature review. The articles used in this synthesis consist of sixteen articles, each of which focuses on Biology in ethnoscience learning, Biology based on ethnoscience learning, and student achievement in both ethnoscience and non-ethnoscience based learning. The articles are published in national and international journals. This research resulted in a new concept which is a synergy between ethnoscience learning tools and student achievement.